Street scene in Nome, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. A Seattle Brewing & Malting Co. Rainier Beer crate is in the foreground. Signs advertise Alaska Title & Abstract Co. and the Gold Digger Printing Office. Warner 145 Filed in Alaska series.